Disiplin Kerja dan Pengaruhnya Terhadap Kinerja Karyawan Pada PT. Prima Rintis Sejahtera Pekanbaru Divisi Unicharm - Dedi Iskamto (Ekonomi Bisnis, 2019)
This study aims to determine the effect of work discipline on the work productivity of employees of PT. Prima Rintis Sejahtera Pekanbaru. This study uses quantitative methods. The number of samples in this study is 49 people, all of whom are employees of PT Prima Rintis Sejahtera.the results of the SPSS data obtained t count value of 5.866 while the t table value is 2.011 which means 5.866> 2.011 then H0 is rejected and Ha is accepted which means that work discipline has a significant effect on the work productivity of employees of PT. Prima Rintis Sejahtera Pekanbaru Unicharm Division.Based on the results of SPSS obtained R2 value of 0.423 or equal to 42.3, which means that work discipline contributes to the influence of work productivity of employees of PT. Prima Rintis Sejahtera Pekanbaru Unicharm Division is 42.3%. And the remaining 57.7% is influenced by other variables outside the working discipline variable.Simple linear regression equation is: Y = 18.144 + 0.737 X Constants of 18.144 if the variable X (work discipline) is 0 then the dependent variable Y (work productivity) remains at 18.144 While the influence of work discipline variables (X) on work productivity variables (Y) is positive that is 0.737, which means that every increase in one-unit work discipline variables will be able to increase the employee productivity variable of PT. Prima Rintis Sejahtera Pekanbaru Unicharm Division at 0.737 units.